2006
DOI: 10.1112/s0024610706022666
|View full text |Cite
|
Sign up to set email alerts
|

Consecutive List Colouring and a New Graph Invariant

Abstract: We consider a variation of the list colouring problem in which the lists are required to be sets of consecutive integers, and the colours assigned to adjacent vertices must differ by at least a fixed integer s. We introduce and investigate a new parameter τ (G) of a graph G, called the consecutive choosability ratio and defined to be the ratio of the required list size to the separation s in the limit as s → ∞.We show that the above limit exists and that, for finite graphs G, τ (G) is rational and is a refinem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…In his thesis [13] and in [14] the second author introduced and studied the consecutive choosability ratio τ (G) which is defined similarly to σ (G) with the difference that all lists are intervals. He showed that τ (G) can be written as τ (G) = a/b with b n. A very similar concept is the circular consecutive choosability, introduced by Lin et al [3] and studied further by Norine et al [6] and Pan and Zhu [9].…”
Section: Discussionmentioning
confidence: 99%
“…In his thesis [13] and in [14] the second author introduced and studied the consecutive choosability ratio τ (G) which is defined similarly to σ (G) with the difference that all lists are intervals. He showed that τ (G) can be written as τ (G) = a/b with b n. A very similar concept is the circular consecutive choosability, introduced by Lin et al [3] and studied further by Norine et al [6] and Pan and Zhu [9].…”
Section: Discussionmentioning
confidence: 99%
“…Besides the choice number, several variations of choosability have also been studied in the literature. One of them is the consecutive choosability, introduced by Waters [10], in which the list-assignment for each vertex is a set of consecutive integers. Another variation, called circular choosability, is motivated by the circular coloring of graphs.…”
Section: Introductionmentioning
confidence: 99%
“…Parallel to the investigation of the consecutive variation of choosability [10], it is natural to consider the consecutive variation of circular choosability in which the list of each vertex is a single closed interval on S(r). This is a notion first introduced and studied by Lin et al [5].…”
Section: Introductionmentioning
confidence: 99%